Evaluation of high-temperature CO2 capture performance of cellulose-templated CaO-based pellets. (1st March 2019) - Sun, Jian; Liang, Cheng; Tong, Xianliang; Guo, Yafei; Li, Weiling; Zhao, Chuanwen; Zhang, Jubing; Lu, Ping
Graphical abstract: Highlights: Cellulose addition improves CO2 capture performance of CaO-based sorbent pellets. Pellet size scarcely affects CO2 uptake of sorbent pellets. Cellulose particle size limitedly affects CO2 uptake of cellulose-templated pellets. Coal combustion causes dramatic CO2 uptake decrease of cellulose-templated sorbent pellets. Abstract: The addition of biomass-based pore-forming templates is an effective approach to improve CO2 capture performance of CaO-based pellets. In this work, cellulose-templated CaO-based pellets were prepared via an extrusion-spherization method. The cyclic CO2 uptake capacity of cellulose-templated pellets was investigated with the variation of pellet size, particle size of cellulose and pre-calcination conditions. It is found that the smaller pellets possess the faster CO2 capture rate during chemical reaction-controlled stage, while the pellet size scarcely affects the ultima CO2 capture capacities of cellulose-templated pellets in 30 min carbonation. Although the addition of cellulose template contributes to enhance CO2 uptake of CaO-based sorbent pellets (over 0.32 g CO2 /g sorbent after 25 cycles), the particle size of cellulose plays a limited role on the CO2 capture performance enhancement effectiveness. Additionally, the cellulose-templated pellets pre-calcined under severe conditions (air calcination and coal combustion) exhibit the inferior, initial CO2 capture capacities due to the excessive sintering as a result of heat release of cellulose and coal combustion. However, severe pretreatments are rewarding to improve the CO2 sorption stability of cellulose-templated sorbent pellets because of the generation of large amounts of micro-sized cavities which are less sensitive to sintering.